All-graphene strain sensor on soft substrate. (May 2017) - Chun, Sungwoo; Choi, Yeonhoi; Park, Wanjun
Abstract: We propose a transparent and stretchable all-graphene strain sensor that can detect various types of strain induced via stretching, bending, and torsion. The sensor is fabricated by introducing single-layer graphene as a force sensing material with a conductive film composed of graphene flake for the electrode. With the exclusive use of flexible materials, the completed strain sensor is fully flexible. Using a serpentine-shaped pattern for the single-layer graphene, the sensor is capable of stretching up to 20% with a high gauge factor (42.2). In addition, the sensor provides functional extension to bi-directional responses. This sensor can detect infinitesimal strain as low as 0.1% with a relative resistance change (ΔR/R0 ) of ∼0.005. Finally, sensitive detection of strains induced via bending and torsion are successfully demonstrated. Graphical abstract: All-graphene strain sensor on soft substrate for the sensor that provides functional extension to bi-directional responses.